2016
DOI: 10.1590/s0080-623420160000600013
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and quality of interaction among oncology nurses: a correlational, cross-sectional study

Abstract: Objective:To explore the severity of Anxiety Symptoms (AS) among Greek oncology nursing personnel, the degree of satisfaction from professional relationships, and potential association between them. Method: A descriptive cross-sectional correlational study was performed in 2 Greek Oncology Hospitals, in 72 members of nursing personnel. Hamilton Anxiety Scale was used for the assessment of AS severity and the Index of Work Satisfaction subscale "Satisfaction from Interaction" for the degree of satisfaction from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
2
16
3
3
Order By: Relevance
“…In general/workers setting, this study supports the results of previous studies, among others: HARS in the Arabic version is valid and reliable to measure work-related stress among working women in Gaza Strip (Aqel & Thabet, 2017), the HAM-A showed good internal consistency to assess the Romanian employees working in non-governmental organizations (Craiovan, 2015), HAM-A can be used globally and is valid and reliable to measure workrelated stress on students (Gupta et al, 2014), HAM-A has a high-reliability index to measure anxiety oncology nursing in Athens, Greece (Karanikola et al, 2016) and the HARS in Greek language was reliable to assess work-related stress in emergency nursing Table 3. Descriptive Characteristics and the Pearson Correlation of Each Data for Internal Consistency of Indonesian Version of the HAM-A Questionnaire (n=98) personnel in Greece (Stathopoulou, Karanikola, Panagiotopoulou, & Papathanassoglou, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general/workers setting, this study supports the results of previous studies, among others: HARS in the Arabic version is valid and reliable to measure work-related stress among working women in Gaza Strip (Aqel & Thabet, 2017), the HAM-A showed good internal consistency to assess the Romanian employees working in non-governmental organizations (Craiovan, 2015), HAM-A can be used globally and is valid and reliable to measure workrelated stress on students (Gupta et al, 2014), HAM-A has a high-reliability index to measure anxiety oncology nursing in Athens, Greece (Karanikola et al, 2016) and the HARS in Greek language was reliable to assess work-related stress in emergency nursing Table 3. Descriptive Characteristics and the Pearson Correlation of Each Data for Internal Consistency of Indonesian Version of the HAM-A Questionnaire (n=98) personnel in Greece (Stathopoulou, Karanikola, Panagiotopoulou, & Papathanassoglou, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…HAM-A was one of the first rating scales developed to measure the severity of anxiety symptoms, being considered one of the most popular assessment instruments widely used rating scales both clinical and research settings/general health psychology, has been widely translated into various languages in the world and is widely used to measure work stress in various types of work (López-Pina, Sánhez-Meca, & Rosa-Alcázar, 2009;Thompson, 2015). Research using HAM-A to assess work-related stress among others: Karanikola et al (2016) who examined anxiety symptoms and quality of interaction among Greek oncology nurses, and Craiovan (2015) which examines burnout, depression, and quality of life among the Romanian employees working in nongovernmental organizations. The HAM-A has been translated into Cantonese for China, French, Urdu, and Spanish, however, the literature that discusses the results of the HAM-A translation, validity and reliability test in the nurse profession in the Indonesian version is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…It might have been due to differences in healthcare systems, types of settings (public vs. private) and oncology units. However, researchers claimed that oncology nurses who have assumed higher levels of workload and tasks with limited number of nursing staffs, become vulnerable to negative outcomes including higher levels of depression, anxiety, and burnout (Escot, Artero, Gandubert, Boulenger, & Ritchie, k., ; Karanikola, Giannakopoulou, Kalafati, Kaite, & Patiraki, ; Tuna & Bayka, ). The second important sources creating stress which were mentioned by the participants of the present study have been referred to emotional demands.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, depression, anxiety, and fatigue are common problems among them (7,8). In addition, Nooryan et al carried out a study on nurses working in Yasuj's Hospitals in Iran and showed that the high prevalence of depression, anxiety, and stress symptoms among nurses is alarming (9).…”
Section: Introductionmentioning
confidence: 99%